Effects of UV Aging on Physical Properties and Physicochemical Properties of ASA Polymer-Modified Asphalt - Xiaolong Sun; Qinyuan Peng; Yongqiang Zhu; Qian Chen; Junshen Yuan; Yunchu Zhu (Advances in Materials Science and Engineering)
The purpose of this study was to characterize and evaluate the effects of UV radiation on the rheological and physicochemical properties of ASA polymer-modified asphalt. The conventional properties (penetration, softening point, ductility, and Brookfield viscosity) of ASA polymer-modified asphalt were tested. Based on rheology, the effect of different UV irradiation times on the high-temperature performance of ASA polymer-modified asphalt was systematically characterized, the thermogravimetric analyzer (TGA) was used to analyze thermogravimetric properties of ASA polymer-modified asphalt, and the micromorphological characteristics of ASA-modified asphalt under different UV irradiation times were characterized by scanning electron microscope (FIB-SEM). The results show that the ASA polymer has a significant effect on the basic properties of asphalt. Compared with the base asphalt, the high-temperature stability of the modified asphalt was decreased, and the low-temperature ductility performance was improved. ASA polymer can effectively reduce the aging effect of ultraviolet radiation on the base asphalt and inhibit the generation of microcracks. ASA polymers improve the thermal stability of asphalt binders. During the aging process, the formation of carbonyl and sulfoxide groups was inhibited, indicating that ASA polymer can effectively delay the UV aging of asphalt.